المهارات النفسية المرتبطة بالأنشطة البدنية والرياضية وعلاقتها بعملية اتخاذ القرار - دولات, ســـــــــفيان; بلعيمش, عبدالصمد (Institut d'éducation physique et sportive/Université de Mostaganem, 2021)
الدراسة : الميارات النفسية المرتبطة باألنشطة البدنية والرياضية و عالقتيا بعممية اتخـــــــــــــــــــــاذ القرار - تيدؼ الدراسة الى معرفة الفروؽ في أبعاد الميارات النفسية لػدى تالميذ الطور الثانوي وارتباطيا باتخاذ القرار والتحسيس بأىمية ىذه الميارات في ميداف عمـ النفس الرياضي وليذا افترض الطالبيف الباحثيف انو يمكف لمميارات النفسية التأثير عمميا في سرعة اتخاذ القرار، وقد احتوت عينة البحث عمى 480 تمميذ مف تالميذ التعميـ الثانوي تـ اخيارىـ بطريقة عشوائية قدرت بنسبة 12%مف مجتمع البحث االصمي, وىذا باالعتماد عمى المنيج الوصفي باألسموب المسحي باستعماؿ المقياسيف والوسائؿ االحصائية المستخدمة وبعدىا استخمص الطالبيف الباحثيف عمى ضوء الدراسة النظرية, الدراسة الميدانية )التجربة االستطالعية ( والدراسة االحصائية لمنتائج الخاـ باستخداـ برنامج *spas* ومف اىـ النتائج المػتوصؿ الييا االسترشاد بنتائج مقياس الميارات النفسية ومقياس اتخاذ القرار التي مف خالليا يكسب التمميذ الخبرة المثمى في مواقؼ المعب وفي مختمؼ الرياضات الجماعية والفردية كما كاف لمميارات النفسية دور فعاؿ في تحسيف اتخاذ القرارات , وفي االخير مف خالؿ ما أسفرت عميو النتائج البحث نوصي بضرورة االىتماـ مف جانب المدرسيف والمدربيف بتنمية الجوانب النفسية التي مف شأنيا اتخاذ قرارات وتحسيف السموؾ لدى تالميذ المرحمة الثانوية ولما ليا مف تأثير فعاؿ في الوصوؿ الى اعمى المستويات الرياضية بالمرحمة الثانوية , وضرورة اجراء دراسات اخرى باستخداـ الميارات النفسية عمى عينات لمراحؿ اخرى وعمى متغيرات اخرى. - الكممـــــــــات المفتاحـــــية: * الميارات النفسية* اتخاذ القرار * المراىقة)المرحمة الثانوية( د Study title: Psychological skills associated with physical and sports activities and their role in the speed of decision-making among is to identify differences in the dimensions of psychological skills in secondary school students and their association with them Quick decision-making and sensitivity to the importance of these skills in the field of psychology Mathematical, which is why researchers have assumed that psychological skills can actually influence the speed of taking Decision, the research sample contained 480 pupils and 80 professors of secondary education They were chosen in a random way that was estimated to be 12 percent of the original research community, and that's based on the descriptive approach Using the measurements and statistical methods used, and then drawing the researchers in the light of the study Theory, field study (exploratory experiment) and statistical study of raw results using *spas * and one of the most important outcomes Psychological skills and the measure of decision-making through which a pupil earns the best experience In play situations and in various group and individual sports, psychological skills have been instrumental in improving Finally, through the results, we recommend the need for attention from teachers and trainers By developing psychological aspects Research summary that will make decisions and improve behave our in secondary school pupils It has an effective impact in reaching the highest levels of secondary school sports and the need for further studies using psychological skills at stages Other and other variables. Key words: _psychological skills _make decision _adolescence
MEPS-2021-1
Keywords: المهــارات النفسية -الأنشـــطة البدنية والرياضية -اتخاذ القرار-المراهقة